2018
DOI: 10.1002/cphc.201701021
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Interacting Quantum Atoms Approach to the S66 and Ionic‐Hydrogen‐Bond Datasets for Noncovalent Interactions

Abstract: The interacting quantum atoms (IQA) method can assess, systematically and in great detail, the strength and physics of both covalent and noncovalent interactions. The lack of a pair density in density functional theory (DFT), which precludes the direct IQA decomposition of the characteristic exchange-correlation energy, has been recently overcome by means of a scaling technique, which can largely expand the applicability of the method. To better assess the utility of the augmented IQA methodology to derive qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 66 publications
(107 reference statements)
1
27
0
Order By: Relevance
“…Its mean value is 0.76±1.36 kcal mol −1 , which corresponds to an average error per atom of 0.06±0.10 kcal mol −1 . The magnitudes of these error estimates are similar to those previously found in the IQA decomposition of formation energies for non‐covalent complexes . We note again that the actual interest of the IQA energy partitioning resides in the atomic and/or fragment‐based IQA components and they have values ranging from ∼0.5 to tens of kcal mol −1 in absolute value (see below) that are well above the mean numerical error per atom.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…Its mean value is 0.76±1.36 kcal mol −1 , which corresponds to an average error per atom of 0.06±0.10 kcal mol −1 . The magnitudes of these error estimates are similar to those previously found in the IQA decomposition of formation energies for non‐covalent complexes . We note again that the actual interest of the IQA energy partitioning resides in the atomic and/or fragment‐based IQA components and they have values ranging from ∼0.5 to tens of kcal mol −1 in absolute value (see below) that are well above the mean numerical error per atom.…”
Section: Resultssupporting
confidence: 83%
“…The IQA quantities are numerically integrated by PROMOLDEN over finite and irregular integration domains (i. e. atomic basins Ω A ) using angular and radial grids in atomic spherical quadratures that are much finer than those typically used by other QM software ,. We employed similar integration settings to those used in previous work and that represent a compromise choice between computational cost and accuracy for small and medium‐sized molecules. Thus, a β‐sphere around each atom was considered (i. e. a sphere completely contained inside the atomic basin), with a radius equal to 60 % the distance of its nucleus to the closest bond critical point in the electron density.…”
Section: Computational Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a systematic effort for validating the use of IQA energies for the study of non-covalent interactions, Suárez et al analysed the binding energies, magnitude of numerical errors, and the fragment and atomic distribution of formation energies within the IQA framework for the S66 and ionic-hydrogen-bond data sets. They shown that this energy partition rigorously quantify atomic and group energy contributions for biomolecular systems [ 88 ].…”
Section: Selected Applications Of the Iqa Methodologymentioning
confidence: 99%